Legal Certainty of Jurisdiction and Authority of the International Criminal Court (ICC) Regarding the Detention of Rodrigo Duterte in the “War on Drugs” Case - Kaloko, Ilhamda Fattah; Harmelia; Putra, Rian Rusmana (JURNAL MERCATORIA, 2025)
This article aims to analyze the relationship between state withdrawal and the jurisdiction of the International Criminal Court (ICC), particularly in the context of the Philippines' decision to withdraw from the Rome Statute. The problem is focused on the legal implications of such a withdrawal, especially in terms of how it influences the ICC's authority to investigate and prosecute crimes committed prior to the effective withdrawal date. This issue is exemplified by the Philippines' controversial "war on drugs" campaign under President Rodrigo Duterte, which has led to the deaths of thousands of civilians and is alleged to constitute serious human rights violations and crimes against humanity. In order to approach this problem, a normative theoretical reference is used to examine international law and the principles of accountability that underpin the ICC’s mandate. Data is collected through a comprehensive analysis of legal texts, court rulings, and relevant case studies. This study concludes that despite a state’s formal withdrawal from the Rome Statute, its responsibility for international crimes committed before the withdrawal remains intact. The ICC continues to hold jurisdiction over such crimes, as demonstrated by its ongoing investigation into the deaths linked to Duterte’s policies. This case highlights significant challenges related to political sovereignty, while also raising critical questions about the tension between national autonomy and global justice.